Ireland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper estimates the cyclical position of the Irish economy. Assessing the business cycle in Ireland is complicated by the open character of its labor market and large presence of globally active multinationals. However, analysis suggests that the Irish economy is in the midst of a cyclical upswing. All methods suggest a positive output gap in 2017, while the labor market shows signs of upward wage pressures, as net immigration has been weak so far. These signs are consistent with a cyclical upswing, amid strong estimated potential output growth, and point to risks of a boom-bust cycle, should the economy continue to push the growth momentum.